Witch Hunt - Conte, Cate (Kensington Books, 2020)
Violet Mooney owns The Full Moon crystal shop in quaint North Harbor, Connecticut. Still grieving her beloved grandmother's recent unexpected death, she takes comfort in her fat orange cat Monty and her work. Not everyone in town is thrilled with her business, however. When disagreeable town councilwoman Carla Fernandez picks a fight over Violet's "voodoo shop," the two have a very public confrontation. Of course, when Carla turns up dead, Violet gets little sympathy from the police as suspect #1. But the shock of two policemen showing up at her door pales in comparison to the sudden appearance of her estranged mother Fiona and a surprise sister, Zoe. What Fiona reveals will rock her world and her sense of self- and reawaken her long-dormant mysterious power. Good thing. She's gonna need it . . .